A rare case report of extrahepatic hepatoblastoma in a child - Sadaf Noureen; Fatima Naumeri; Mamoonullah Asmati; Muhammad Habib Javed (Journal of the Pakistan Medical Association, 2023)
Hepatic malignancies account for 1-4% of all childhood solid tumours and Hepatoblastoma is the most common malignant liver tumour in children. Its extrahepatic origin is rare. Here we present the case of a three-year-old boy who came with a large non-tender mass in the right upper abdomen for six months. Ultrasound abdomen revealed a huge heterogenous mass anterior to the right kidney and inferior to the liver with internal vascularity and calcifications, mimicking a neuroblastoma. Tru-cut needle biopsy showed foetal-type hepatoblastoma. After neoadjuvant chemotherapy, the tumour was explored. It was found to be adherent to the inferior surface of the liver with no capsular breech. Hence differentiating it from exophytic growth of hepatoblastoma. The tumour was completely resected. The postoperative course was uneventful and adjuvant chemotherapy was given. So far only a few cases of extrahepatic hepatoblastoma have been reported. Keywords: Extrahepatic, hepatoblastoma, suprarenal, tumor, excision.